Cerebral saturation in cardiac arrest patients measured with near-infrared technology during pre-hospital advanced life support. Results from Copernicus I cohort study. (August 2018) - Genbrugge, Cornelia; De Deyne, Cathy; Eertmans, Ward; Anseeuw, Kurt; Voet, Dirk; Mertens, Ilse; Sabbe, Marc; Stroobants, Jan; Bruckers, Liesbeth; Mesotten, Dieter; Jans, Frank; Boer, Willem; et al.
Abstract: Aim: To date, monitoring options during pre-hospital advanced life support (ALS) are limited. Regional cerebral saturation (rSO2 ) may provide more information concerning the brain during ALS. We hypothesized that an increase in rSO2 during ALS in out-of hospital cardiac arrest (OHCA) patients is associated with return of spontaneous circulation (ROSC). Methods: A prospective, non-randomized multicenter study was conducted in the pre-hospital setting of six hospitals in Belgium. Cerebral saturation was measured during pre-hospital ALS by a medical emergency team in OHCA patients. Cerebral saturation was continuously measured until ALS efforts were terminated or until the patient with sustained ROSC (>20 min) arrived at the emergency department. To take the longitudinal nature of the data into account, a linear mixed model was used. The correlation between the repeated measures of a patient was handled by means of ​a random intercept and a random slope. Our primary analysis tested the association of rSO2 with ROSC. Results: Of the 329 patients 110 (33%) achieved ROSC. First measured rSO2 was 30% ± 18 in the ROSC group and 24% ± 15 in the no-ROSC group (p = .004; mean ± SD). Higher mean rSO2 values were observed in the ROSC group compared to the no-ROSC group (41% ± 13 versus 33% ± 13 respectively; p < 0.001). The median increase in rSO2, measured from start until two minutes before ROSC, was higher in the ROSC group (ROSC group 17% (IQR 6–29)) than in the no-ROSC group (8% (IQR 2–13); p < 0.001). An increase in rSO2 above 15% was associated with ROSC (OR 4.5; 95%CI 2.747–7.415; p < 0.001). Conclusion: Regional cerebral saturation measurements can be used during pre-hospital ALS as an additional marker to predict ROSC. An increase of at least 15% in rSO2 during ALS is associated with a higher probability of ROSC.